Fuel Cell Catalyst Layers and Membrane-Electrode Assemblies Containing Multiblock Poly(arylene ether sulfones) Bearing Perfluorosulfonic Acid Side Chains. Issue 10 (1st January 2018) - Lee, Hsu-Feng; Killer, Miho; Britton, Benjamin; Wu, Yang; Nguyen, Huu-Dat; Iojoiu, Cristina; Holdcroft, Steven
Abstract : A sulfonated poly(arylene ether sulfone) multiblock copolymer bearing perfluorosulfonic acid side chains has been studied as both the membrane and cathode catalyst layer ionomer in fuel cell membrane-electrode assemblies. The multi-block, hydrocarbon-backbone polymer was designed to possess good conductivity with low ion exchange capacity and low water sorption to mimic perfluorosulfonic acid ionomers, but without the synthetic difficulty. A H2 /O2 -fuel cell power density of 1080 mW·cm −2 was achieved at 80°C, 100% RH using membrane-electrode assemblies incorporating the sulfonated poly(arylene ether sulfone) membrane and traditional PFSA ionomer in the catalyst layer. An accelerated stress test using 30% RH, 90°C, H2 /Air demonstrated durability to open circuit potentials of more than 400 h, which is 4 times longer than for Nafion 211. No membrane thinning was observed over the same period, which is attributed to low gas crossover and inhibition of membrane degradation reactions, despite the rate of water transport across the membrane remaining high. Cathode catalyst layers fabricated using 20 wt% sulfonated poly(arylene ether sulfone) as the ionomer exhibited comparable power densities to benchmark PFSA MEAs, under high current densities, over a wide range of operational relative humidities, demonstrating that hydrocarbon-backbone, solid polymer electrolytes hold technological promise as both the membrane and catalyst layer ionomer in fuel cell membrane-electrode-assemblies.